Implementation of Criminal Responsibility for Perpetrators of Criminal Acts of Insulting the Sundanese Ethnic Group Through Internet Media - Sujasmin Sujasmin; Emaliawati Emaliawati (Universitas Islam Sultan Agung, 2026)
The crime of insulting the Sundanese ethnic group is one of the most dangerous crimes of insulting Indonesian citizens, as the Sundanese ethnic group is a West Javanese tradition that reflects a democratic state. In the era of technological and information development (internet media), news spreads rapidly, and its spread can also lead to hostility and hatred between ethnic groups, religions, races, and groups (SARA). One example is Resbob's statement, which is suspected of being a criminal act of insulting the Sundanese ethnic group, and its news has spread, ultimately causing public unrest. This study aims to determine: 1. How to interpret the law regarding the crime of insulting the Sundanese ethnic group related to Resbob's statement and 2. How to apply criminal liability to the perpetrator for the crime of insulting the Sundanese ethnic group related to Resbob'sstatement. The results of this study, in the form of a legal interpretation of insulting the Sundanese ethnic group related to Resbob's statement, can use a historical interpretation of the law and a teleological/sociological interpretation. Insults against the Sundanese ethnic group are regulated under Article 28 paragraph (2), Article 45A paragraph (2) of the ITE Law, Articles 242-243 of the Criminal Code in conjunction with Law No. 1 of 2026, as a criminal act of insulting a population group. The application of criminal liability for the perpetrator in this case is reviewed based on a. the doctrine of cause and effect/individualization theory, b. the qualifications for offenses known as insulting a population group, c. the legal basis for the occurrence of other crimes in the ITE Law and the Criminal Code, and d. criminal liability based on the formulation of the crime in statements aimed at hostility towards individuals or groups based on ethnicity, religion, race, and intergroup relations (SARA).